Nonlinear diffusivity dependence on dimensions - Janavičius, Arvydas Juozapas; Turskienė, Sigita; Žilinskas, Kęstutis (Lietuvos matematikos rinkinys, 2015)
The nonlinear diffusion equation corresponds to the diffusion processes which can occur with a finite velocity. This statement is not satisfied in Fick’s second law or linear diffusion equation. The processes by which different materials mix in the result of the random Brownian motions of atoms, molecules and ions can be exactly described only with presented nonlinear equation. It was important in practice that theoretically profiles fit with the experimental profiles tail region, but get good coincidence between diffusion experiments and the classical solutions is impossible. By using obtained theoretical solutions for two and three-dimensional cases we can provide more exact modeling of all the stages of a planar transistor formation.
Keywords: nonlinear diffusion equation; diffusion coefficients in higher dimensional; approximate analytical solution